Efficient bioleaching of high-magnesium low-grade copper-nickel sulfide ore: optimization and mechanisms - Duo-Rui Zhang; Dai-Ying Wei; Jing Zhang; Hong-Rui Chen; Zi-Jie Jin; Lei Zheng (Minerals Engineering, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Engineering Naematelia aurantialba as a Robust Synthetic Biology Chassis: Stable Episomal Vector Construction and Metabolic Optimization for Enhanced Polysaccharide Synthesis - Yuhang Ma; Yingfeng Wang; Ming Zhang; Liang Sun; Rui Wang; Yian Gu; Peng Lei; Hong Xu (Bioresource Technology, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Integrative multi-omics analysis identifies FAM3D as a prognostic tumor suppressor in cervical cancer - Yanbin Chen; Yu Hong; Dongjun Wei; Lianjiao Fan; Dian Tao; Rui Zhang; Hongwei Yang (Functional & Integrative Genomics, 2026)

Biomimetic platelet membrane-camouflaged liposomes with RBCs hitchhiking enable efficient targeting and suppression of lung metastasis - Kehui Zhu; Xunyi You; Ke Zhang; Yee Shan Wong; Hong Wang; Rui Zhong; Jiaxin Liu; Ye Cao (Chemical Engineering Journal, 2026)

Iterative precursor rebalancing improves phenazine-1-carboxylic acid production in engineered Pseudomonas chlororaphis - Sheng-Jie Yue; Peng Huang; Chen Song; Song Li; Rui Lian Yao; Wei Wang; Xue-Hong Zhang; Pablo I. Nikel; Hong-Bo Hu (Bioresource Technology, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Electronic, optical and mechanical properties, and photocatalytic water splitting of Janus ZrHfCO2 under biaxial strain: First-principles prediction - Rui-Wen Yan; Hao Zhang; Xiao-Hong Li; Rui-Zhou Zhang; Hong-Ling Cui (Journal of Environmental Chemical Engineering, 2026)

Oxidized Late Devonian arc intrusion in the Jiangda area, eastern Tibet: Implication for heterogeneous porphyry Cu-Au fertility of Paleo-Tethyan arc magmas - Rui Ma; Ming-Liang Huang; Lei-Luo Xu; Jing-Jing Zhu; Bao-Di Wang; Hong-Rui Zhang; Rui-Zhong Hu; Xing-Chun Zhang; Xian-Wu Bi (Journal of Asian Earth Sciences, 2026)

Polysaccharide–metal complexes for precision nutrition: Intelligent delivery, gut microbiota modulation and gut–brain communication - Xiaoliang Zhang; Rui Tang; Zhi Wang; Hong Zhuang (Food Bioscience, 2026)

Interfacial electronic coupling in Bi2O3/COF heterostructures for high-performance supercapacitors - Rui Zhang; Hong-xia Gao; Yu-ting Zhao; Li Li; Yan Lv; Xue-yan Wu; Jixi Guo; Rui Xue (Chemical Engineering Journal, 2026)

Harnessing a MMP-sensitive fluorescent probe for in-situ and reversible monitoring MMP alteration in dual color based on aggregation/monomer mechanism - Mengmeng Wei; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Yi Qian; Jing Xu; Xiaoyan Tang; Jiaojiao Liu; Shenqiang Wang; Tingwang Jiang; Xifeng Yang; Xuekun Hong; et al. (Analytica Chimica Acta, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Elucidation of a novel skatole degradation pathway and key genes in Rhodococcus rhodochrous S3 - Kaihua Pan; Rui Fan; Qi Xie; Yike Lyu; Bingjie Xu; Qian Zhu; Mingliang Zhang; Qian Li; Weihao Zhu; Yanni Huang; Qing Hong; Lina Sun (Journal of Hazardous Materials, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Mapping and environmental control analysis of susceptibility to retrogressive thaw slumps in the central Qinghai Tibet Plateau - Ruikai Hong; Xu He; Jichao Lv; Bin Xiao; Age Shama; Zhihan Yang; Yunjie Yang; Bo Zhang; Dujuan Zhang; Rui Zhang (Remote Sensing Applications: Society and Environment, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Dynamic response of muscle-inspired hierarchical tubular structure under lateral shock loading - Chang Ye Ni; De Long Cheng; Jian Hong Zhang; Gao Meng Cai; Rui Zhang; Tian Jian Lu (Engineering Structures, 2026)

Enriched numerical manifold method with closed-form solutions for the crack-tip singularity in elastic fracture - Hua-rui ZHU; Hong ZHANG; Xi-long LI; Wei WU; Sun-jun HU; Gen-hua SHI (Computers and Geotechnics, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

A crop-growth-coupled simulation-optimization approach for canal system scheduling within water-energy-food nexus - Hui Wu; Chenglong Zhang; Qiong Yue; Rui Chen; Hong Li (Agricultural Systems, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Classification of SARS-CoV-2 Variants Through the Epistatic Circos Plots with Convolutional Neural Networks - Bo Jing; Kai-Rui Zhang; Hong-Li Zeng; Erik Aurell (Journal of Molecular Evolution, 2026)
The COVID-19 pandemic has profoundly affected global health, driven by the remarkable transmissibility and mutational adaptability of the SARS-CoV-2 virus. Although five variants of concern, Alpha, Beta, Gamma, Delta, and Omicron, have been identified, the classification task in this study is formulated using four classes: Alpha, Delta, Omicron, and Else, reflecting the sequence availability and temporal coverage of the dataset. Here, we develop an integrative framework that combines direct coupling analysis (DCA), Circos-based visualization, and convolutional neural networks (CNNs) to characterize lineage-specific epistatic signatures from large-scale SARS-CoV-2 genomic sequences. DCA-inferred pairwise mutational couplings were transformed into Circos images, which were then used as inputs for CNN-based classification models. The proposed framework achieved robust variant classification, with the best-performing model reaching a weighted-average $$F_1\text {-score}$$ of $$98.68± 0.75%$$ and an AUC close to 1. Additional temporal holdout analyses showed that the framework retained reasonable predictive capability across evolutionary time, yielding a weighted-average $$F_1\text {-score}$$ of 87.85%.

Revealing the rotational growth of carbon nanotubes by atmospheric environmental transmission electron microscopy - Rui-Hong Xie; Hao An; Lili Zhang; Zichu Zhang; Mengke Zou; Yinghui Pu; Bingsen Zhang; Feng Ding; Chang Liu (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Zinc and Iron(III) complexes of carboxymethyl Ganoderma polysaccharide: Chelation mechanism, structural features, and in vitro biological activity - Luyu Zhang; Xiaoliang Zhang; Xinyu Qi; Xiaolong Chen; Rui Zhao; Hong Zhuang (Food Bioscience, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

Drought Duration Alters the Soil Water Threshold Corresponding to the Leaf Photosynthetic Efficiency of Potato in Semi-arid Regions - Yang Yang; Hong Zhao; Shi-qiong Yang; Di-hua Cai; Kai Zhang; Yu-rui Tang; Yue Qi; Peng-cheng Huang (Potato Research, 2026)

Inhibiting hydrolytic enzyme activity and slowing carbohydrate digestion using lotus seed epicarp phenolic extracts - Congcong Wang; Rui Chen; Lingxiao Gong; Hong Xu; Jie Liu; Huijuan Zhang (Natural Product Research, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Macrophages with ITIH4 overexpression attenuate inflammatory responses and regulate intestinal epithelial cells - Jing Li; Zhuoqi Zhao; Jun Fei; Rui Zhang; Liya Pan; Ying Xiang; Li Hong; Zhiyan Zhan (Inflammation Research, 2026)

Integrating carbon-based nutrient fertilization for urban soil management: Impacts on plant growth and microbial communities - Xihui Sun; Hong Liu; Rui Yu; Song Li; Xuemiao Tian; Huiwen Zhang; Lixin Niu; Yanlong Zhang (Urban Forestry & Urban Greening, 2026)

The evaluation to combined toxic effects of polypropylene microplastics and benzo[a]pyrene on macrophage cells - Ye-xuan Zhang; Rui Hou; Si-si Chen; Xue-wen Guo; Hong-juan Chen; Li Mao; Wei-juan Zheng; Hong-zhen Lian (Science of The Total Environment, 2026)

The mechanism of reducing the oil content of fried instant noodles by adding sugar alcohol: microstructure, surface properties and molecular structure - Rui He; Xiaomeng Ma; Ju Chen; Chengrong Zheng; Dingwu Zhang; Chong Liu; Jing Hong; Binghua Sun; Mei Liu; Jiaying Shang; Zipeng Liu; Xueling Zheng (Food Research International, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

A deep learning multi-branch network method for landslide susceptibility mapping in the Sichuan-Tibet transportation corridor - Jichao Lv; Ruikai Hong; Xin Bao; Renzhe Wu; Xu He; Guoxiang Liu; Rui Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Heavy metal removal and concurrent stabilization of pig manure via constructed wetland-microbial fuel cell driven by sponge iron: Microbial response and mechanistic insight - Qingyun Zhang; Wanqing Jin; Xiaolu Tang; Xiang Mao; Rui Zuo; Yajun Hong; Dayong Xu (Process Safety and Environmental Protection, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Effects of mung bean addition on quality and starch anti-digestion mechanism of oat noodles - Rui-xian Shang; Wei-feng Zhang; Zi-hao Tu; Xiu-juan Ren; Yan-xia An; Gui-Hong Yin; Jian Zhang; Yang Zhao (Journal of Cereal Science, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Highly transparent sponge-like hydrogel substrates regulated by NaCl for efficient solar water evaporation - Ke Cheng; Yangyang Li; Hong Ni; Rui Zhang; Wei Wei; Jing Zhou; Jing Yuan (Chemical Engineering Journal, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Study on the irradiation control of urease activity and its solidification of red clay to enhance radon reduction - Yuanyuan Tang; Rui Liang; Jia Wei; Yiqing Sun; Weihang Peng; Fubing Li; Chengyu Zhang; Changshou Hong (Journal of Environmental Radioactivity, 2026)

A Hybrid CUBE-IForest Approach for Outlier Detection in Multibeam Bathymetry - Rui Han; Yukai Hong; Xibin Han; Yi Zhang; Shunming Hu; Yuan Huan; Xiaodong Cui; Xiaohu Li (Journal of Marine Science and Engineering, 2026)
With the rapid development and widespread application of multibeam echo-sounding systems, large-scale and high-resolution seafloor topography can be efficiently acquired, enabling precise mapping of seabed terrain. However, due to complex oceanographic conditions, instrumental noise, and acoustic interferences, the acquired multibeam data often contain outliers that deviate from the true seafloor surface. These outliers can distort the representation of seafloor topography, adversely affecting subsequent geological analysis and engineering applications. To address this issue, a hybrid outlier detection method combining CUBE filtering with the Isolation Forest (IForest) algorithm, termed CUBE-IForest, is proposed. The method first employs CUBE filtering to remove gross outliers based on local uncertainty estimation, followed by the application of IForest to identify subtle anomalies in the refined data, achieving hierarchical detection of outliers. Experimental results based on in situ multibeam bathymetric data from the northeastern Pacific demonstrate that compared with traditional filtering methods the CUBE-IForest approach significantly improves detection accuracy and reduces both false positive and false negative rates by approximately 30%, confirming its efficiency and reliability in seafloor mapping and analysis.

Unravelling the antifungal mechanism of phytic acid on Aspergillus flavus development and aflatoxin B1 biosynthesis - Guang Yang; Shuwen Li; Jingrong Liu; Huayan Wang; Rui Hong; Yimei Zhang; Andong Gong (Food Additives & Contaminants: Part A, 2026)

Caseazins R−Y, cytotoxic podocarpane diterpenoids from Casearia kurzii - Xue-Wen Wu; Qiong Wei; Xia Pu; Chun-Mei Cha; Rui Li; Yin-Qiao Huang; Rui-Han Zhang; Xiao-Li Li; Hong-Liang Li; Wei-Lie Xiao (Phytochemistry, 2026)

Time-series InSAR with phase gradient stacking and slope-constrained clustering for large-scale landslide detection in the Sichuan-Tibet Region - Jichao Lv; Rui Zhang; Kun Fang; Kun Chen; Age Shama; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Advances and Challenges in Constructing Bone Organoids Using Cells Derived from Human Pluripotent Stem Cells: A Review - Zhengyang Xie; Maoying Liu; Shaodong Wang; Ting Meng; Hong Zou; Yian Guan; Yameng Song; Yirong Kong; Liying Qin; Chuan Zhang; Rui Zhang; Ping Zhou (Stem Cell Reviews and Reports, 2026)

Numerical investigation of simple support spacer grid effect on critical heat flux in a typical 5 × 5 rod bundle - Yushun Lu; Rui Zhang; Jianquan Liu; Hong Peng (Annals of Nuclear Energy, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Improved PSO-VMD seismic signal denoising method combined with modified wavelet transform - Hui Sun; Hong-yong Ren; Rui Chen; Xing-guo Huang; Wei Zhang; Yan-song Li; Jian Zhang; Yu-bo Yue (Applied Geophysics, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

Temporal transcriptomics reveal crucial networks underlying jasmonate-mediated diurnal floret opening and closure in rice - Rui Zhang; Xiaohui Xi; Xiaozhou Hu; Dan Xiang; Yi Wang; Yu Pan; Xi He; Yuhan Zhang; Lilan Hong; Yuanzhu Yang; Ming Zhou (Science China Life Sciences, 2025)

Dynamic response of ceramic-reinforced metallic corrugated sandwich structures under combined blast-fragment loading - Chang-ye Ni; Cong Luo; Lu-sheng Qiang; Xin-yi Bai; Jia-le Wu; Jian-hong Zhang; Rui Zhang (Engineering Structures, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

The organic matrix: An in-depth review of kerogen and its significance - Kouqi Liu; Hongyan Qi; Zhizhong Wang; Bo Liu; Yamin Wang; Zhengchen Zhang; Hong Zhang; Rui Yang; Liangliang Jiang; Mehdi Ostadhassan (Fuel, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

Silkworm sand-based bio-organic fertilizers reshape rhizosphere microbiomes and modulate soil chemistry for sustainable management of Myrica rubra decline - Leidong Hong; Chunlai Hong; Weijing Zhu; Fengxiang Zhu; Weiping Wang; Tao Zhang; Rui Guo; Xingjiang Qi; Xiuqin Zou; Yanlai Yao (Plant and Soil, 2025)

Application of platelet-rich plasma lysate combined with hyaluronic acid microneedles for the treatment of alopecia - Zhengxin Suo; Yingcan Xu; Along Zhang; Ye Cao; Jiaxin Liu; Hong Wang; Rui Zhong (Drug Delivery and Translational Research, 2025)

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficient solar-driven tandem catalysis for biomass valorization: selective C C bond cleavage to synthesize xylitol - Liangdong Hu; Huiyan Zhang; Zupeng Chen; Nengchao Luo; Lian-Hua Xu; Kai Wu; Longfei Hong; Sheng Chu; Rui Xiao (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Intelligent Alignment Control for Floating Raft Air Spring Mounting System Under Coupled Hull–Raft Deformation - Jian-Wei Cheng; Wen-Jun Bu; Ze-Chao Hu; Jun-Qiang Fu; Hong-Rui Zhang; Liang Shi (Journal of Marine Science and Engineering, 2025)
Shaft alignment is adversely affected by the increasingly severe coupled hull–raft deformation in deep-diving, highly integrated submersibles, thereby compromising operational safety and potentially amplifying vibration noise. To address to this issue, this paper investigates an intelligent alignment control method for the floating raft air spring mounting system (ASMS) applied to marine propulsion unit (MPU) under coupled hull–raft deformation conditions. A multi-objective alignment control algorithm was developed based on the NSGA-II optimization method within an N-step receding horizon optimal control framework, enabling simultaneous achievement of shaft alignment attitude adjustment, hull deformation compensation, raft deformation suppression, and pneumatic energy consumption. Experimental validation was conducted on two distinct ASMS prototypes to evaluate the control algorithm. Tests performed on the ASMS for MPU (MPU-ASMS) prototype demonstrated effective compensation of hull-induced deformations, maintaining shaft alignment offsets within ±0.3 mm and angularities within ±0.5 mm/m. Concurrently, experiments on the floating raft ASMS for the stern compartment (SC-FR-ASMS) achieved precise control of axial offsets within ±0.3 mm, angularities within ±0.5 mm/m, and vertical displacements of critical monitoring points within ±1 mm. The adaptive control strategy additionally proved effective in suppressing raft deformation while simultaneously optimizing pneumatic energy consumption. This research provides robust theoretical and technical foundations for intelligent vibration isolation systems in deep-sea equipment to accommodate extreme-depth-induced hull deformation and large-scale raft deformation.

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Removal of disinfection residual bacteria in UV222, UV222/H2O2 and UV222/peroxymonosulfate systems: what is the safe usage for wastewater reclamation - Rui Gao; Shu-Hong Gao; Jun Li; Fang Huang; Yanmei Zhao; Jingni Xie; Yusheng Pan; Wanying Zhang; Aijie Wang (Water Research, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Multi-target directed ligands design of 1-O-Acetylbritannilactone derivatives: Dual anti-neuroinflammatory and acetylcholinesterase inhibitory activities - Yan-Peng Liang; Qian Gao; Hong Chen; Rui Ma; Xiao-Bo Zhao; Xiao-Jie Jin; Jian Zhang; Yan-Ping Shi; Wei Ha (Phytochemistry Letters, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Substrate type-driven differences in interfacial microbial community and pathogenic risk: Clay, microplastics and activated carbon - Taishuo Zhang; Wenfu Wang; Xiang Zhi; Xiaoqian Ye; Rui Wang; Jiarui Zhao; Jiamin Dai; Hong Qiang; Peng Liu; Hanzhong Jia (Gondwana Research, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Effects of Microclimates on Species Richness of Epiphytic and Non‐Epiphytic Bryophytes Along a Subtropical Elevational Gradient in China - Zun Dai; Hong‐Wei Zhang; Hong Qian; Min Li; Rui‐Ping Shi; Zhao‐Chen Zhang; Jian Zhang; Hong‐Qing Li; Jian Wang (Journal of Biogeography, 2025)
Aim Biodiversity patterns along elevational gradients have been well documented for vascular plants and terrestrial vertebrates, but we know relatively little about the elevational patterns of bryophytes and their underlying mechanisms, especially the effect of forest microclimate on epiphytic and non‐epiphytic bryophytes. Here we study the influence of microclimates on the richness of epiphytic and non‐epiphytic bryophytes as a whole, and for liverworts and mosses separately, in forests along an elevational gradient ranging from 369 to 1476 m in a subtropical region. Location Mt. Tianmu in eastern China. Methods We sampled bryophytes in each of 16 vegetation plots, each of the size of 20 by 20 m, along the elevational gradient and distinguished between mosses and liverworts and between epiphytic and non‐epiphytic species. We measured climate conditions at local sites. Species richness of bryophytes along the elevational gradient was related to six microclimate variables, using correlation and regression analyses and a variation partitioning approach. Results Overall, species richness of bryophytes showed a slightly decreasing trend with elevation, and epiphytic and non‐epiphytic bryophyte richness showed different elevational patterns. Compared to non‐epiphytic bryophytes, species richness of epiphytic bryophytes was more influenced by air microclimate. We also found that species richness of bryophytes was influenced by both microclimate extreme variables and microclimate seasonality variables. In sum, utilising in situ air and soil microclimatic monitoring data, our study offers a more accurate assessment of the relationship between bryophyte species richness and their habitats. Main Conclusions Our results highlight the importance of considering the ecological differences between mosses and liverworts, and distinguishing between microhabitats of sampled bryophyte assemblages when exploring the patterns and drivers of bryophyte diversity along elevational gradients.

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Multi-layer landscape design of urban spontaneous plant community: A case study in Zhengzhou, China - Wangxin Su; Zeqi Zhai; Wenhui Zhang; Rui Li; Jiayi Li; Yang Liu; Wenqian Jiang; Hong Wei; Nan Guo; Yonghua Li (Urban Forestry & Urban Greening, 2025)

The curvilinear relationship between perceived stress and spicy food craving in Young females: A non-linear mediation effect of positive emotional experience of spicy food consumption - Huizhen Qiu; Yidan Rui; Yuchen Zhang; Meiqi Hu; Shuang Zheng; Nanlin Xu; Jiaqi Jing; Pengfei Han; Hong Chen; Xiao Gao (Food Quality and Preference, 2025)

Silver carp by-product hydrolysate: A promising mucin substitute for stimulating Akkermansia muciniphila growth and metabolic activity - Huijuan Zhang; Rui Zhang; Shengjun Chen; Ruifang Feng; Sam K.C. Chang; Yongkang Luo; Hui Hong; Yuqing Tan (Food Bioscience, 2025)

Time-series InSAR landslide three-dimensional deformation prediction method considering meteorological time-delay effects - Jichao Lv; Rui Zhang; Xin Bao; Renzhe Wu; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2025)

The chromosome-scale genomes of two cultivated safflowers (Carthamus tinctorius) provide insights into the genetic diversity resulting from domestication - Shuo Liu; Saimire Aishan; Qiuyu Liu; Lu Lv; Kang Ma; Kangjun Fan; Kehui Zhang; Yonghua Qin; Gang Li; Xueli Hu; Zunhong Hu; Junwei He; et al. (Theoretical and Applied Genetics, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Surfactant-assisted spent fried oil for gasification slag flotation: An innovative approach for simultaneous waste oil utilization and slag separation - Rui Han; Shizhi Ruan; Anning Zhou; Zhen Li; Hong Wang; Ningning Zhang (Journal of Environmental Chemical Engineering, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Solar-driven transient Lewis acid sites for synergistic efficient photocatalytic isomerization of glyceraldehyde - Liangdong Hu; Lian-hua Xu; Chenjun Yang; Longfei Hong; Kai Wu; Sheng Chu; Longlong Ma; Shurong Wang; Rui Xiao; Huiyan Zhang (Chemical Engineering Journal, 2025)

Highly efficient separation of anthracene and carbazole in crude anthracene by composite extractants with low viscosity - Yuanyuan Wang; Wenhai Zhang; Danting Wang; Rui Ma; Lili Ai; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang; Hong Meng (Chemical Engineering Journal, 2025)

A stable and high-contrast color/fluorescence dual-mode stimuli-responsive poly (imino sulfone) for anti-counterfeiting and encryption - Tengning Ma; Hong Luo; Weiyuan Zhou; Huijuan Zhang; Rui Yuan; Qing He; Ying Huang; Li Yang; Guanjun Chang (Chemical Engineering Journal, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Coplanar two-dimensional Cu-MOF with dual-Cu sites for electrocatalytic CO2 reduction to C2H4 - Yu-Peng Han; Zi-Rui Wang; Ya-Yu Yan; Qiao-Hong Li; Ping Shao; Hai-Xia Zhang; Li-Li Han; Fei Wang; Jian Zhang (Chemical Engineering Journal, 2025)

Cyclodextrin-based delivery systems for chemical and genetic drugs: Current status and future - Yikun Gao; Le Sun; Chu Qiao; Yuqing Liu; Yang Wang; Rui Feng; Hong Zhang; Youxi Zhang (Carbohydrate Polymers, 2025)

Effect of Particle Size, Sphericity, and Distribution on Seepage in Granular Porous Media - Bo-bo Xiong; Rui Kuang; Ping Zhang; Bin Tian; Hong-hu Gao; Qian Zheng; Yu-qin Li (Geotechnical and Geological Engineering, 2025)

Selenium Treatment Alleviates the Inhibition Caused by Nep-L Gene Knockdown in Silkworm (Bombyx mori) - Ting-Ting Hong; Fei Hu; Wen-Jie Ge; Rui Zhang; Juan Du; Kiran Thakur; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

The role of sulfur cycle in new particle formation: Cycloaddition reaction of SO3 to H2S - Haijie Zhang; Wei Wang; Liang Fan; Junling Li; Yanqin Ren; Hong Li; Rui Gao; Yisheng Xu (Journal of Environmental Sciences, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Recent progress in Cu-based electrocatalysts for CO2 reduction - Ruo-Zheng Xiong; Hui-Min Xu; Hong-Rui Zhu; Zhi-Jie Zhang; Gao-Ren Li (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Eleutherococcus giraldii (Harms) Nakai: a review of botany, traditional uses, phytochemistry, pharmacology and quality control - Ling Li; Jie Zhang; Li-wen Zhong; Rui Gu; Shi-hong Zhong (Phytochemistry Reviews, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

A new benzophenone derivative from Aspergillus fumigatus WJ-131 - Jia-Qi Liu; Sheng-Qi Zhang; Xiu-Hong Wu; Shuai-Xing Liu; Rui-Dang Yang; Liang Deng; Le Cai (Natural Product Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Microwave replacing traditional concentrating process to promote the synthesis of mumefural in Prunus mume extract - Teng Long Miao; Shan Qin; Xiao Hong Chen; Long Yun Chen; Yan Qing Han; Yan Li Yuan; Xin Rui; Wei Li; Qiu Qin Zhang (Food Research International, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Effects of chitosan/eugenol-loaded IRMOF-3 nanoparticles composite films on reactive oxygen species metabolism and microbial community dynamics in postharvest strawberries - Yuyue Qin; Hongda Yu; Kejun Chen; Rui Cui; Jianxin Cao; Zhengxuan Wang; Zhi-Hong Zhang; Thanapop Soteyome (Food Bioscience, 2025)

Potential of probiotic-fermented Flos sophorae as a functional food: Enhanced anti-hyperuricemic activity and modulation of volatile components - Rui Cui; Cong Zhang; Zhen-Hui Pan; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Flower-structured CoP@MoS2-x S-scheme heterojunction photocatalysts for enhanced hydrogen evolution and selective biomass oxidation - Jia Zhang; Jiliang Ma; Rui Cui; Weikang Ling; Min Hong; Runcang Sun (Chemical Engineering Journal, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

A rapid increase of groundwater in 2021 over the North China Plain from GPS and GRACE observations - Rui Zhang; Yujie Peng; Nengfang Chao; Qi Ou; Gang Chen; Zhengtao Wang; Hong Zhu; Bing Liu; Zixin Zhang (GPS Solutions, 2025)

Travel time calculation of seismic waves on complex surfaces using the group marching method - Ping Zhang; Fan-chang Meng; Xiao-hang Zhao; Jian-hui Deng; Rui Chen; Hong-yong Ren; Xiang-yu Tan; Gong-min Chen (Applied Geophysics, 2024)

Evaluation of water distribution and uniformity of sprinkler irrigation based on harmonic analysis and finite element method - Xiaofang Chen; Rui Chen; Jian Wang; Hong Li; Weibin Zhang (Biosystems Engineering, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Cyclic response and load transfer mechanism of suction bucket jackets supporting offshore wind turbines in soft clay - Baofeng Zhang; Rui Liu; Lizhong Wang; Xuetao Wang; Lilin Wang; Wei Li; Yi Hong (Ocean Engineering, 2024)

Enhanced flotation separation of coal gasification fine slag by composite collectors containing polar fatty acids - Ningning Zhang; Mengyan Cheng; Rui Han; Zhen Li; Anning Zhou; Hong Wang (Journal of Environmental Chemical Engineering, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Granular insights into occupant behaviours and CO2 emissions in the UK - Ruiming Zhang; Tongyu Zhou; Rui Jing; Hua Cai; Tao Lin; Kai Wang; Huanye He; Guoqin Zhang; Xian Wu; Hong Ye (Journal of Cleaner Production, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

The fate of organic compounds in organic waste during torrefaction and implications for its valorization - Yi Hu; Rui Yang; Yiping Wu; Xuejiao Chen; Wei Lin; Hong Wang; Zhiyong Qi; Dongdong Zhang; Lin Ouyang (Environmental Pollution, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

Tetracycline adsorption on sludge-bamboo biochar prepared by gradient modification and co-pyrolysis: Performance evaluation and mechanism insight - Lijia Chen; Haiqing Yang; Ran Hong; Xuehui Xie; Rui Zuo; Xiaoying Zhang; Saisai Chen; Dayong Xu; Qingyun Zhang (Journal of Environmental Chemical Engineering, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

A clinical-radiomics nomogram based on spectral CT multi-parameter images for preoperative prediction of lymph node metastasis in colorectal cancer - Qian Li; Rui Hong; Ping Zhang; Liting Hou; Hailun Bao; Lin Bai; Jian Zhao (Clinical & Experimental Metastasis, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

A multi-spatial scale analysis of anthropogenic nitrogen and phosphorus inputs in a large river basin: environmental effect and policy impact - Chenning Deng; Zeqian Zhang; Chaozheng Zhang; Rui Xu; Chong Nie; Qingjia Meng; Tiansen Zou; Hong Li; Jia Wu; Queping Yang (Regional Environmental Change, 2024)

Shoot and Root Traits are Associated with Varying Soil Phosphorus Supply in Chinese Cabbage - Hou Sai-sai; Pu Zi-tian; Zhang Rui-fang; Zhang Chi; Wang Hong; Wang Xin-xin; Zhao Jian-jun (Journal of Soil Science and Plant Nutrition, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Quartz trace element geochemistry and internal morphology as proxies for provenance characterization: Results from the Marwar basin, NW India - Jun Zhang; Rui Li; Manoj K. Pandit; Ting-Guang Lan; Qing Xiong; Yuan-Bao Wu; Jun-Hong Zhao; Wei Wang (Precambrian Research, 2024)

Exploring the spatial patterns of landslide susceptibility assessment using interpretable Shapley method: Mechanisms of landslide formation in the Sichuan-Tibet region - Jichao Lv; Rui Zhang; Age Shama; Ruikai Hong; Xu He; Renzhe Wu; Xin Bao; Guoxiang Liu (Journal of Environmental Management, 2024)

Mechanism study of synergistic aluminum extraction and purification by ammonium for high-value conversion of secondary aluminum dross - Wen Deng; Qinglin Xie; Rui Zhou; Haorui Tuo; Xueming Liu; Hong Deng; Zhang Lin (Journal of Environmental Chemical Engineering, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Response of GFRP suction bucket in clay during installation - Hai-lei Kou; Zhao-tun An; Yong-kang Wang; Hong-rui Zhang; Xi-xin Zhang (Ocean Engineering, 2024)

Body size: A hidden trait of the organisms that influences the distribution of antibiotic resistance genes in soil - Rui Guo; Yanlai Yao; Zhe Zhang; Chunlai Hong; Fengxiang Zhu; Leidong Hong; Weijing Zhu (Journal of Hazardous Materials, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Manipulating cationic ordering toward highly efficient and zero-thermal-quenching cyan photoluminescence - Hongzhi Zhang; Hong Li; Conglin Liu; Hongming Jiang; Junpeng Li; Yuxin Liu; Jiayi He; Rui Wang; Wanbiao Hu; Jing Zhu (Chemical Engineering Journal, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Improved seed yield and phosphorus accumulation in soybean are associated with the enhanced root exudates in south-west China - Hong-Lan Zhang; Nian Liang; Rui Dong; Chang-An Liu; Chun-Ling Hao; Kadambot H. M. Siddique; Jin He (Plant and Soil, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Resources recovery from coal gasification residue by combined hydrocyclone and vibrating screen and characterization of separated products - Ningning Zhang; Fuqiang Zhao; Rui Han; Zhen Li; Zhanglei Zhu; Jinzhou Qu; Hong Wang; Anning Zhou (Process Safety and Environmental Protection, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

A polypyrrole-dopamine/poly(vinyl alcohol) anisotropic hydrogel for strain sensor and bioelectrodes - Shuang Chen; Bingyan Guo; Jiajun Yu; Zhuojun Yan; Rui Liu; Chaojie Yu; Zhongming Zhao; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Occurrence, physicochemical properties and environmental behavior of polychlorinated dibenzothiophenes: A comprehensive review and future perspectives - Chunmeng Ye; Yong Tu; Hong Ling; Yong Chen; Yang Liu; Rui Zhang; Xuesheng Zhang (Environmental Research, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

The lncRNA20718-miR6022-RLPs module regulates tomato resistance to Phytophthora infestans - Jia-hui Zhang; Hong-bo Wei; Yu-hui Hong; Rui-rui Yang; Jun Meng; Yu-shi Luan (Plant Cell Reports, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

Electrospinning is a potential way for preparing edible plant protein-based nanofibers with porous surface using safflower seed meal - Yanling Yang; Chuang Peng; Dong Zeng; Zhengjie Yang; Xiaohu Wang; Shuang Zhang; Yucheng Bai; Lujing Kuang; Lizhi Guo; Yonghua Qin; Hairong Xiong; Jiawei Wan; et al. (Food Hydrocolloids, 2024)

Fe(VI) oxidation of synthetic phenolic antioxidants: Kinetics, influencing factors, transformation mechanism and toxicity - Xiaoxue Pan; Fengtao Sun; Min Wang; Hong Sun; Rui Zhang; Mingbao Feng; Xuesheng Zhang (Chemical Engineering Journal, 2024)

Non-radical mediated reduced graphene oxide/polypyrrole catalytic ceramic membrane-PDS system for source control of SMX - Rui Wang; Hong You; Zhipeng Li; Jing Zhao; Mu Li; Jing Zhu; Guoyu Zhang; Xianshi Wang; Haoran Leng; Shaojie Qi; Binghan Xie (Chemical Engineering Journal, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Microbial mechanism of biochar addition to reduce N2O emissions from soilless substrate systems - Xiaofeng Liang; Wanlai Zhou; Rui Yang; Dongdong Zhang; Hong Wang; Qiaozhen Li; Zhiyong Qi; Yuzhong Li; Wei Lin (Journal of Environmental Management, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Pyroptosis induction synergized with IDO inhibition of ternary biomedicine for photodynamic activated tumor immunotherapy - Ali Chen; Ni Yang; Wei Zhang; Rongrong Zheng; Rui Yu; Renjing Kong; Yuqing Wang; Hong Cheng; Xiyong Yu; Shiying Li (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Whole-genome analysis of the benzoic acid-degrading bacterium Bacillus halotolerans B28 to reveal its phytoprobiotic effects - Dandan Wang; Li Sun; Hong Yu; Chengkai Zhang; Xin Guan; Mengliang Wang; Rui Cheng; Chao Wang; Zhihong Xie (International Biodeterioration & Biodegradation, 2023)

Hydrophobic aggregation via partial Gal removal affects solution characteristics and fine structure of tamarind kernel polysaccharides - Rui Guo; Xianbao Sun; Yuxing Kou; Hong Song; Xujiao Li; Lihua Song; Taolei Zhao; Hui Zhang; Deshun Li; Yanfang Liu; Zibo Song; Jieli Wu; et al. (Food Hydrocolloids, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Enhancing biomass oxidation with carbon nitride nanosheets ring inserted on C. I. Pigment Yellow 53 photocatalysts for simultaneous CO and lactic acid production - Weikang Ling; Jiliang Ma; Zhendong Liu; Rui Cui; Junqiang Zhang; Xinze Li; Min Hong; Runcang Sun (Chemical Engineering Journal, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Evaluation of sustainable development efficiency in Chinese provinces- based on closed-loop feedback three-stage dynamic network slack-based measure model - Yanyong Hu; Rui Zhang; Jiaxi Wu; Xiaotong Qie; Hong Liu (Process Safety and Environmental Protection, 2023)

A new norditerpenoid and other components from Ajuga macrosperma and their bioactivity - Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Hong-Ping He; Rui Yang; Hua-Yi Jiang (Phytochemistry Letters, 2023)

Effects of Fe and cost-effective media composition on arsenopyrite bioleaching by Sulfobacillus thermosulfidooxidans - Hong-Rui Chen; Duo-Rui Zhang; Xiao-Juan Zhao; Qian Li; Yu-Ting Liang; Eva Pakostova; Yan Zhang; Yong-Bin Yang (Chemical Engineering Journal, 2023)

Realgar-Induced Neurotoxicity: Crosstalk Between the Autophagic Flux and the p62-NRF2 Feedback Loop Mediates p62 Accumulation to Promote Apoptosis - Rui Feng; Jieyu Liu; Zhao Yang; Tiantian Yao; Ping Ye; Xiuhan Li; Jiaxin Zhang; Hong Jiang (Molecular Neurobiology, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Transcriptome Analysis of the Mouse Medial Prefrontal Cortex in a Chronic Constriction Injury Model - Qi-Min Zheng; Zi-Rui Zhou; Xin-Yu Hou; Ning Lv; Yu-Qiu Zhang; Hong Cao (NeuroMolecular Medicine, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

International Nuclear Medicine Consensus on the Clinical Use of Amyloid Positron Emission Tomography in Alzheimer’s Disease - Mei Tian; Chuantao Zuo; Ali Cahid Civelek; Ignasi Carrio; Yasuyoshi Watanabe; Keon Wook Kang; Koji Murakami; Valentina Garibotto; John O. Prior; Henryk Barthel; Yihui Guan; Jiaying Lu; et al. (Phenomics, 2023)
Alzheimer’s disease (AD) is the main cause of dementia, with its diagnosis and management remaining challenging. Amyloid positron emission tomography (PET) has become increasingly important in medical practice for patients with AD. To integrate and update previous guidelines in the field, a task group of experts of several disciplines from multiple countries was assembled, and they revised and approved the content related to the application of amyloid PET in the medical settings of cognitively impaired individuals, focusing on clinical scenarios, patient preparation, administered activities, as well as image acquisition, processing, interpretation and reporting. In addition, expert opinions, practices, and protocols of prominent research institutions performing research on amyloid PET of dementia are integrated. With the increasing availability of amyloid PET imaging, a complete and standard pipeline for the entire examination process is essential for clinical practice. This international consensus and practice guideline will help to promote proper clinical use of amyloid PET imaging in patients with AD.

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

One-dimensional self-weight consolidation of layered soil under variable load and semi-permeable boundary condition - Hong-Xin Chen; Shi-Jin Feng; Zhang-Wen Zhu; Liang Gao; Zhang-Long Chen; Shu-Rui Wang (Computers and Geotechnics, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Novel adsorbent synthesized from red mud and acid mine drainage for enhanced contaminant removal: Industrial waste transformation, adsorbent performance and metal(loid) removal mechanisms - Duo-Rui Zhang; Hong-Rui Chen; Jin-Lan Xia; Zhen-Yuan Nie; Xiao-Juan Zhao; Eva Pakostova (Chemical Engineering Journal, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Physicochemical Characterization of Three Active Pharmaceutical Ingredients for Compound Glycyrrhizin Solid Formulation and Compatibility Analysis via Thermal and Non-thermal Techniques - Xiang-yun Xie; Zhan-ying Chang; Chun-li Chen; Liang Zhang; Mei Wang; Cheng Tang; Hong-rui Xue; Xiao-li Gao (Journal of Pharmaceutical Innovation, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Two-step sequential bio-oxidation of arsenopyrite catalyzed by a mesophilic bacterium eliminates hazardous Fe(III)/As-bearing products and enhances mineral dissolution - Hong-Rui Chen; Qian Li; Xiao-Juan Zhao; Duo-Rui Zhang; Eva Pakostova (Chemical Engineering Journal, 2023)

Highly stability Cu+ species in hollow Cu2O nanoreactors by modulating cavity size for CO2 electroreduction to C2+ products - Rui Zhang; Feifei Chen; Haokun Jin; Yong Zhang; Xiaoya Hao; Yingda Liu; Tianming Feng; Xinghua Zhang; Zunming Lu; Weihua Wang; Feng Lu; Hong Dong; et al. (Chemical Engineering Journal, 2023)

Parameter Study on How the Cervical Disc Degeneration Affects the Segmental Instantaneous Centre of Rotation - Hong Zhang; Dacheng Sang; Bin Zhang; Ya-Nan Ren; Xin Wang; Jing-Jing Feng; Cheng-Fei Du; Baoge Liu; Rui Zhu (Journal of Medical and Biological Engineering, 2023)

A model description of beta oscillations in the external globus pallidus - Mingming Chen; Yajie Zhu; Rui Zhang; Renping Yu; Yuxia Hu; Hong Wan; Dezhong Yao; Daqing Guo (Cognitive Neurodynamics, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Characteristics, sources and health risk assessment of atmospheric carbonyls during multiple ozone pollution episodes in urban Beijing: Insights into control strategies - Yunfeng Li; Hong Li; Xin Zhang; Yuanyuan Ji; Rui Gao; Zhenhai Wu; Manfei Yin; Lei Nie; Wei Wei; Guohao Li; Yafei Wang; Mei Luo; et al. (Science of The Total Environment, 2023)

Slab dehydration and magmatism in the Kurile arc as a function of depth: An investigation based on B-Sr-Nd-Hf isotopes - Hong-Yan Li; Chao Xie; Jeffrey G. Ryan; Chuan-Mao Yang; Rui-Peng Zhao; Chao Zhang; Yi-Gang Xu (Chemical Geology, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Ecological toxicity of Cd, Pb, Zn, Hg and regulation mechanism in Solanum nigrum L. - Rui Zhao; Xiufeng Cao; Xinxin Li; Tao Li; Hong Zhang; Xiaowei Cui; Zhaojie Cui (Chemosphere, 2023)

Kidney Mesenchymal stem cells alleviate cisplatin-induced kidney injury and apoptosis in rats - Rui-ning Liang; De-qi Yan; Xing-ping Zhang; Xu Chen; Wen-hui Zhang; Hong-lin Jia (Tissue and Cell, 2023)

Inhibition of ice recrystallization by tamarind (Tamarindus indica L.) seed polysaccharide and molecular weight effects - Xianbao Sun; Rui Guo; Yuxing Kou; Hong Song; Taijie Zhan; Jinhong Wu; Lihua Song; Hui Zhang; Fan Xie; Jiangmei Wang; Zibo Song; Yan Wu (Carbohydrate Polymers, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Bioactive icetexane and abietane diterpenes from Isodon phyllopodus - Rui Deng; Juan Zou; Chen-Liang Zhao; Ye-Meng Yang; Chuen Fai Ku; Yu Zhu; Zheng-Ming Liang; Jiang-Hai Ye; Lu-Tai Pan; Hong-Jie Zhang (Natural Product Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Insights into production and consumption processes of nitrous oxide emitted from soilless culture systems by dual isotopocule plot and functional genes - Wei Lin; QiaoZhen Li; Wanlai Zhou; Rui Yang; Dongdong Zhang; Hong Wang; Yujia Li; Zhiyong Qi; Yuzhong Li (Science of The Total Environment, 2023)

Formation mechanism of typical aromatic sulfuric anhydrides and their potential role in atmospheric nucleation process - Haijie Zhang; Rui Gao; Hong Li; Yunfeng Li; Yisheng Xu; Fahe Chai (Journal of Environmental Sciences, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Plant-associated Microbe System in Treatment of Heavy Metals–contaminated Soil: Mechanisms and Applications - Zhiming Ren; Rui Cheng; Peng Chen; Yuanyuan Xue; Hong Xu; Yao Yin; Guangtuan Huang; Wei Zhang; Lehua Zhang (Water, Air, & Soil Pollution, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Effects and mechanism of ultrasound treatment on Chironomus kiiensis eggs - Bo-dong Liu; Hao-tao Dong; Hong-wei Rong; Rui-jian Zhang (Environmental Science and Pollution Research, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Response of bacterial communities in saline-alkali soil to different pesticide stresses - Juan Che; Yan Lei Zhu; Yan Hong Li; Rui Zhang; Zhi Yong Ruan; Wei Zhang (Environmental Science and Pollution Research, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Positron Emission Tomography Molecular Imaging for Phenotyping and Management of Lymphoma - Xiaohui Zhang; Han Jiang; Shuang Wu; Jing Wang; Rui Zhou; Xuexin He; Shufang Qian; Shuilin Zhao; Hong Zhang; Ali Cahid Civelek; Mei Tian (Phenomics, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Responses of estuarine circulation to the morphological evolution in a convergent, microtidal estuary - Rui Zhang; Bo Hong; Lei Zhu; Wenping Gong; Heng Zhang (Ocean Science, 2022)
The Huangmaohai estuary (HE) is a funnel-shaped microtidal estuary in the west of the Pearl River Delta (PRD) in southern China. Since China reformed and opened up in 1978, extensive human activities have occurred and greatly changed the estuary's topography and modified its hydrodynamics. In this study, we examined the morphological evolution by analyzing remote sensing data with ArcGIS tools and studied the responses of hydrodynamics to the changes in topography from 1977 to 2010 by using the Delft3D model. We took the changes in estuarine circulation during neap tides in dry seasons as an example. The results show that human reclamation caused a narrowing of the estuary, and channel dredging deepened the estuary. These human activities changed both the longitudinal and lateral estuarine circulations. The longitudinal circulation was observed to increase with the deepening and narrowing of the estuary. The lateral circulation experienced changes in both the magnitude and pattern. The momentum balance analysis shows that when the depth and width changed simultaneously, the longitudinal estuarine circulation was modulated by both the channel deepening and width reduction, in which the friction, pressure gradient force, and advection terms were altered. The analysis of the longitudinal vortex dynamics indicates that the changes in the vertical shear of the longitudinal flow, lateral salinity gradient, and vertical mixing were responsible for the change in the lateral circulation. The changes in water depth are the dominant factors affecting lateral circulation intensity. This study has implications for sediment transport and morphological evolution in estuaries heavily impacted by human interventions.

Correction to: A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Change detection in remote sensing images based on manifold regularized joint non-negative matrix factorization - Weidong Yan; Xinxin Liu; Jinhuan Wen; Jinfeng Hong; Sa Zhang; Rui Zhao (Earth Science Informatics, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Impacts of anthropogenic disturbances on microbial community of coastal waters in Shenzhen, South China - Rui Zhang; Wen-chao Liu; Yu Liu; Hong-lian Zhang; Zhi-hui Zhao; Ling-yun Zou; Yu-chun Shen; Wen-Sheng Lan (Ecotoxicology, 2021)

Optimizing staggered-grid finite-difference method based on the least-squares combination of the square window function - Chao-pu Chen; Hong Liu; Zhi-yang Wang; Wen-lei Bai; Cheng-fang Zhang; Zi-rui Meng (Applied Geophysics, 2021)

TREM-1 Exacerbates Neuroinflammatory Injury via NLRP3 Inflammasome-Mediated Pyroptosis in Experimental Subarachnoid Hemorrhage - Pengfei Xu; Ye Hong; Yi Xie; Kang Yuan; Juanji Li; Rui Sun; Xiaohao Zhang; Xiaolei Shi; Rongrong Li; Jiaonan Wu; Xinfeng Liu; Wei Hu; et al. (Translational Stroke Research, 2021)

Discovery of novel DGAT1 inhibitors by combination of machine learning methods, pharmacophore model and 3D-QSAR model - Hui Zhang; Chen Shen; Hong-Rui Zhang; Wen-Xuan Chen; Qing-Qing Luo; Lan Ding (Molecular Diversity, 2021)

The correlation of altitude with gingival status among adolescents in western China: a cross-sectional study - Zhiwu Wu; Rui Zhang; Li Cheng; Ruilie Cai; Hong Chen; Ran Cheng; Tao Hu (Environmental Geochemistry and Health, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Precise frequency transfer model suitable for short baseline link based on GPS single-differenced observations with ambiguity resolution - Rui Tu; Pengfei Zhang; Rui Zhang; Lihong Fan; Junqiang Han; Ju Hong; Jinhai Liu; Xiaochun Lu (Acta Geodaetica et Geophysica, 2021)

Cracking behaviors and strength of rock-like samples with steps of different geometries under shear stress - Hui-lin Le; Ji-hong Wei; Shao-rui Sun; Chu-chu Zhang (Journal of Mountain Science, 2021)

A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Phytochemical constituents, chemotaxonomic significance and anti-arthritic effect of Eucommia ulmoides Oliver staminate flowers - Rui Li; Lanlan Nie; Qing Wang; Danwei Ouyang; Lei Zhang; Ying Yuan; Yanlong Hong; Jianying Wang; Xiao Hu (Natural Product Research, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Mechanical characteristics of soil-rock mixtures containing macropore structure based on 3D modeling technology - Yong Liu; Shao-rui Sun; Ji-hong Wei; Jing-lei Song; Yong-xiang Yu; Wei He; Ji-xing Zhang (Journal of Mountain Science, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Late Early-Cretaceous Magma Mixing in the Langqi Island, Fujian Province, China: Evidences from Petrology, Geochemistry and Zircon Geochronology - Liangliang Huang; Liyuan Wang; Hong-Rui Fan; Musen Lin; Wenhui Zhang (Journal of Earth Science, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Comparative study on the bioaccumulation of lead, cadmium and nickel and their toxic effects on the growth and enzyme defence strategies of a heavy metal accumulator, Hydrilla verticillata (L.f.) Royle - Hong Zhang; Ling-Lei Zhang; Jia Li; Min Chen; Rui-Dong An (Environmental Science and Pollution Research, 2020)

Characterization and fine mapping of Arabidopsis RLL3, a locus required for DNA demethylation pathway - Wei Miao; Jie Dai; Yumei La; Chong Lu; Jianzhen Zhang; Xinyue Hong; Shaoxia Zhou; Qianqian Wang; Xiangyu Wang; Qi Rui; Feng Tan; Honggui La (Molecular Genetics and Genomics, 2020)

U.S. national parks accessibility and visitation - Xing-ju Shen; Rui-hong Huang; Jin-shan Zhang (Journal of Mountain Science, 2019)

An improved method for detecting BeiDou signal-in-space anomalies from precise ephemerides - Lihong Fan; Rui Tu; Rui Zhang; Zengji Zheng; Xiaochun Lu; Jinhai Liu; Xiaodong Huang; Ju Hong (Acta Geodaetica et Geophysica, 2019)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Chemical constituents from the leaves of Melia azedarach - Jin Zeng; Rui-Jing Ma; Ling Wang; Sheng-Nan Zhang; Hong-Zhi Song; Yang Yang; Qin-Gang Tan (Natural Product Research, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Putting It All Together: Adding Value to the Global Ocean and Climate Observing Systems With Complete Self-Consistent Ocean State and Parameter Estimates - Patrick Heimbach; Ichiro Fukumori; Christopher N. Hill; Rui M. Ponte; Detlef Stammer; Carl Wunsch; Jean-Michel Campin; Bruce Cornuelle; Ian Fenty; Gaël Forget; Armin Köhl; Matthew Mazloff; et al. (Frontiers in Marine Science, 2019)

Transgenic Rice Overexperessing a Tomato Mitochondrial Phosphate Transporter, SlMPT3;1, Promotes Phosphate Uptake and Increases Grain Yield - Guo-hong Yu; Sheng-cai Huang; Rui He; Ying-zhang Li; Xian-guo Cheng (Journal of Plant Biology, 2018)

Spatial patterns of interprovincial mountain geographical names in China and implications for regional governance - Sheng-rui Zhang; Ying-jie Wang; Hong-run Ju; Tong-yan Zhang; Dai-chao Li; Lei Fang; Ying-ying Wang (Journal of Mountain Science, 2018)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Determination of Ocean Tide Loading Displacement by GPS PPP with Priori Information Constraint of NAO99b Global Ocean Tide Model - Hong Zhao; Qin Zhang; Rui Tu; Zhi Liu (Marine Geodesy, 2018)

Residents’ environmental conservation behaviour in the mountain tourism destinations in China: Case studies of Jiuzhaigou and Mount Qingcheng - Yu-ling Zhang; Jie Zhang; Hong-ou Zhang; Ruo-yang Zhang; Yang Wang; Yong-rui Guo; Zong-cai Wei (Journal of Mountain Science, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Ne2 encodes protein(s) and the altered RuBisCO could be the proteomics leader of hybrid necrosis in wheat (Triticum aestivum L.) - Si Rui Pan; Xing Lai Pan; Qian Ying Pan; Yin Hong Shi; Li Zhang; Yun Fan; Yan Rui Xue (Journal of Genetics, 2017)

Waterlogging risk assessment based on self-organizing map (SOM) artificial neural networks: a case study of an urban storm in Beijing - Wen-li Lai; Hong-rui Wang; Cheng Wang; Jie Zhang; Yong Zhao (Journal of Mountain Science, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

A new helvolic acid derivative from an endophytic Fusarium sp. of Ficus carica - Xi-Ai Liang; Yang-Min Ma; Hong-Chi Zhang; Rui Liu (Natural Product Research, 2016)

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Cloning and molecular characterization of Myb transcription factors from Leymus (Poaceae: Trticeae) - Ying-xia Lei; Yan Zhang; Yang-yi Li; Jian-Jun Lai; Gang Gao; Hai-qin Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

A retrospective study of the occurrence of ischemic-type biliary lesions post liver transplantation - Rui Shi; Ya-Min Zhang; Yong-Lin Deng; Hong Zheng; Cheng Pan; Zhong-Yang Shen (Science China Life Sciences, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Adaptation to climate change impacts on water demand - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; En-hong Guan; Yong-xiang Wu; Juan Gao; Rui-min He (Mitigation and Adaptation Strategies for Global Change, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Systematic Review by Multivariate Meta-analyses on the Possible Role of Tumor Necrosis Factor-α Gene Polymorphisms in Association with Ischemic Stroke - Yu-Ming Niu; Hong Weng; Chao Zhang; Rui-Xia Yuan; Jin-Zhu Yan; Xiang-Yu Meng; Jie Luo (NeuroMolecular Medicine, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Diagnosis of Small Bowel Obstruction using Targeted Enterography During Nasointestinal Decompression - Rui-hong Li; De-chun Li; Qin-zhong Tian; Ping Wu; Xin-hui Zhang (Cell Biochemistry and Biophysics, 2015)

Effect of the CYP2D6 gene polymorphism on postoperative analgesia of tramadol in Han nationality nephrectomy patients - Hong Dong; Shu-jun Lu; Rui Zhang; Dong-dong Liu; Yan-zhuo Zhang; Chun-yu Song (European Journal of Clinical Pharmacology, 2015)

Characterization of genomic sequence of a drought-resistant gene TaSnRK2.7 in wheat species - HONG YING ZHANG; WEI LI; XIN GUO MAO; RUI LIAN JING (Journal of Genetics, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Historic water consumptions and future management strategies for Haihe River basin of Northern China - Xiao-jun Wang; Jian-yun Zhang; Zhi-feng Yang; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Hong-wei Liu (Mitigation and Adaptation Strategies for Global Change, 2015)

The impact of the cognition of landscape experience on tourist environmental conservation behaviors - Yu-ling Zhang; Jie Zhang; Hong-Lei Zhang; Shao-wen Cheng; Yong-rui Guo; Jin-hai Ma; Jing-rong Sun (Journal of Mountain Science, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Cooling and exhumation of the mid-Jurassic porphyry copper systems in Dexing City, SE China: insights from geo- and thermochronology - Xuan Liu; Hong-rui Fan; Noreen J. Evans; Geoffrey E. Batt; Brent I. A. McInnes; Kui-feng Yang; Ke-zhang Qin (Mineralium Deposita, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Precise and Economical Dredging Model of Sediments and Its Field Application: Case Study of a River Heavily Polluted by Organic Matter, Nitrogen, and Phosphorus - Rui Zhang; Fan-Xin Zeng; Wu-Jun Liu; Raymond J. Zeng; Hong Jiang (Environmental Management, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Effects of vascular endothelial growth factor B on proliferation and migration in EA.Hy926 cells - Guang-hong Zhang; Rui Qin; Shui-hua Zhang; He Zhu (Molecular Biology Reports, 2014)

Total Glucosides of Peony Attenuates 2,4,6-Trinitrobenzene Sulfonic Acid/Ethanol-Induced Colitis in Rats Through Adjustment of Th1/Th2 Cytokines Polarization - Yabing Zhang; Rui Zhou; Feng Zhou; Hong Cheng; Bing Xia (Cell Biochemistry and Biophysics, 2014)

Molecular Cloning and Transcriptional Analysis of the Putative AGAMOUS Homolog AcAG in Onion (Allium cepa) - Hong-You Li; Rui Zhao; Chan Wang; Li-Ying Zhang; Hong Zhao; Yong-Qin Wang (Plant Molecular Biology Reporter, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

How immunogenetically different are domestic pigs from wild boars: a perspective from single-nucleotide polymorphisms of 19 immunity-related candidate genes - Shanyuan Chen; Rui Gomes; Vânia Costa; Pedro Santos; Rui Charneca; Ya-ping Zhang; Xue-hong Liu; Shao-qing Wang; Pedro Bento; Jose-Luis Nunes; József Buzgó; Gyula Varga; et al. (Immunogenetics, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Petrogenesis and tectonics of late Permian felsic volcanic rocks, eastern Qiangtang block, north-central Tibet: Sr and Nd isotopic evidence - Hong-Rui Zhang; Tian-Nan Yang; Zeng-Qian Hou; Yu-Cai Song; Yan Ding; Xian-Feng Cheng (International Geology Review, 2013)

Re–Os molybdenite ages and zircon Hf isotopes of the Gangjiang porphyry Cu–Mo deposit in the Tibetan Orogen - Cheng-Biao Leng; Xing-Chun Zhang; Hong Zhong; Rui-Zhong Hu; Wei-De Zhou; Chao Li (Mineralium Deposita, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Screening level ecological risk assessment for synthetic musks in surface water of Lake Taihu, China - Guang-Hui Guo; Feng-Chang Wu; Hong-Ping He; Rui-Qing Zhang; Hui-Xian Li (Stochastic Environmental Research and Risk Assessment, 2013)

Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Metal-Binding Activity of the Soluble Recombinant Pig Metallothionein 1A Expressed in Escherichia coli - Dongbo Sun; Hong Zhang; Guojun Wu; Qinghe Zhu; Siwen Lv; Donghua Guo; Rui Wu; Jun Bao (Biological Trace Element Research, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

A New bis(rhodamine)-Based Fluorescent Chemosensor for Fe3+ - Xiaopo Chen; Huijie Hong; Rui Han; Di Zhang; Yong Ye; Yu-fen Zhao (Journal of Fluorescence, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Phylogenetic relationships between Leymus (Poaceae, Triticeae) and related diploid Triticeae species based on isozyme and genome-specific random amplified polymorphic DNA (RAPD) markers - Rui-Wu Yang; Min-Han Zhong; Xue-Mei Zou; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou (Plant Biosystems, 2012)

Metagenomic analysis of DNA viruses in a wastewater treatment plant in tropical climate - Hideyuki Tamaki; Rui Zhang; Florent E. Angly; Shota Nakamura; Pei‐Ying Hong; Teruo Yasunaga; Yoichi Kamagata; Wen‐Tso Liu (Environmental Microbiology, 2012)
Summary Viruses have been detected in the different stages of wastewater treatment plants (WWTPs) at concentrations of 10 8 –10 10 ml −1 of virus‐like particles (VLPs), 10–1000 times higher than in natural aquatic environments, suggesting that WWTPs can be considered as an important reservoir and source of viruses. This study revealed novel diversity and function with the DNA viral communities in the influent, activated sludge, anaerobic digester, and effluent of a domestic WWTP using metagenomics. WWTP was a very specific environment, with less than 5% of the > 936 000 metagenomic sequences obtained (∼70–119 Mbp per sample) similar to sequences present in other environmental viromes. Many viruses found in the WWTP were novel, resulting in only 82% were shared. These data suggested that VLPs of most viral types could be present between 1 and 30 days in the process before they were discharged. Viruses in WWTP and the discharged ones can have potential impacts on the functioning of the wastewater treatment system and on the dynamics of microbial community in the surrounding aquatic environments respectively.

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of Copper Exposure on Expression of Glutathione-Related Genes in Acidithiobacillus ferrooxidans - Jin-lan Xia; Shun Wu; Rui-yong Zhang; Cheng-gui Zhang; Huan He; Hong-chen Jiang; Zhen-yuan Nie; Guan-zhou Qiu (Current Microbiology, 2011)

Dynamics of vegetation and soil carbon and nitrogen accumulation over 26 years under controlled grazing in a desert shrubland - Zhi-Yu Zhou; Feng-Rui Li; Shan-Ke Chen; Hong-Rong Zhang; Guangdi Li (Plant and Soil, 2011)

RETRACTED ARTICLE: Cytotoxic activities of tubeimoside-2 on human hepatoma HepG2 cells by induction of G2/M phase arrest and apoptosis in a p53-dependent manner - Ying-Yong Zhao; Xu Chao; Yongmin Zhang; Li-Jun Sun; Hong Zhang; Rui-Chao Lin; Xuefeng Shen; Wen-Ji Sun (Apoptosis, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Salicylic Acid Reduces Napropamide Toxicity by Preventing Its Accumulation in Rapeseed (Brassica napus L.) - Jing Cui; Rui Zhang; Guo Lin Wu; Hong Mei Zhu; Hong Yang (Archives of Environmental Contamination and Toxicology, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Identity of an ABA-activated 46 kDa mitogen-activated protein kinase from Zea mays leaves: partial purification, identification and characterization - Haidong Ding; Aying Zhang; Jinxiang Wang; Rui Lu; Hong Zhang; Jianhua Zhang; Mingyi Jiang (Planta, 2009)

Tenascin-R distinct domains modulate migration of neural stem/progenitor cells in vitro - Wenhui Huang; Luyong Zhang; Rui Niu; Hong Liao (In Vitro Cellular & Developmental Biology - Animal, 2009)

Mechanisms underlying low [Ca2+]o-induced increased excitability of hippocampal neurons - Wei-Dong Yue; Yun-Hong Zhang; Feng Gu; Jing Wang; Ji-Ye Zhang; Rui-Min Gu (Neuroscience Bulletin, 2008)

Protective effect of butin against hydrogen peroxide-induced apoptosis by scavenging reactive oxygen species and activating antioxidant enzymes - Rui Zhang; Sungwook Chae; Kyoung Ah Kang; Mei Jing Piao; Dong Ok Ko; Zhi Hong Wang; Doek Bae Park; Jae Woo Park; Ho Jin You; Jin Won Hyun (Molecular and Cellular Biochemistry, 2008)

Activities and Toxicity of a Novel Plant Growth Regulator 2-Furan-2-yl-[1,3] Dioxolane - Tian Rui Ren; Yan Hong Xie; Wei Wen Zhu; Yong Hong Li; Ye Zhang (Journal of Plant Growth Regulation, 2007)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Genome constitutions of Hystrix patula, H. duthiei ssp. duthiei and H. duthiei ssp. longearistata (Poaceae: Triticeae) revealed by meiotic pairing behavior and genomic in-situ hybridization - Hai-qin Zhang; Rui-wu Yang; Quan-wen Dou; Hisashi Tsujimoto; Yong-hong Zhou (Chromosome Research, 2006)

The Genetic Diversity Among Leymus Species Based on Random Amplified Microsatellite Polymorphism (RAMP) - Rui-Wu Yang; Yong-Hong Zhou; Ying Zhang; You-Liang Zheng; Chun-Bang Ding (Genetic Resources and Crop Evolution, 2006)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Biophysical studies of a ruthenium(II) polypyridyl complex binding to DNA and RNA prove that nucleic acid structure has significant effects on binding behaviors - Hong Xu; Yi Liang; Peng Zhang; Fen Du; Bing-Rui Zhou; Jun Wu; Jian-Hong Liu; Zhi-Gang Liu; Liang-Nian Ji (JBIC Journal of Biological Inorganic Chemistry, 2005)

Evolution of urban system in new economic circumstances and planning countermeasures - Jing-xiang Zhang; Qi-yan Wu; Fu-hong Rui (Chinese Geographical Science, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)